Palliative care patients’ attitudes and openness towards psilocybin-assisted psychotherapy for existential distress - Wang, Julia Ruixi; Mendez Araque, Samuel J.; Micciche, Gina; McMillan, Andrew; Coughlin, Emily; Mattiola, Rosalie; English, Diana; Kaliebe, Kristopher (Frontiers in Psychiatry, 2024)
Introduction: Patients with incurable illnesses often experience existential distress, profoundly impacting their well-being. Current medical approaches have limitations in addressing these burdens. Psilocybin, a promising psychedelic compound, may offer therapeutic benefits. This pilot survey study aimed to investigate the attitudes and openness toward psilocybin-assisted psychotherapy (PAT) among patients with incurable illnesses. The objective is to assess patients' attitudes toward PAT and identify potential barriers and concerns, including exploring the association between beliefs in psilocybin's therapeutic benefits and interest in receiving this treatment.The survey study was conducted at the Tampa General Hospital Palliative Care Outpatient office in the United States. Participants were 32 English-fluent patients, aged 18 or older, with incurable illnesses. The survey included demographic questions, a validated tool to measure existential distress, and questions about knowledge and concerns regarding psilocybin. Attitudes toward PAT and interest in its future use were assessed using Likert scale responses.Results: Among the 31 analyzed participants, 51.6% expressed interest in future psilocybin treatment, while 32.3% did not indicate interest. Belief in the psilocybin's therapeutic benefits for stress and anxiety significantly correlated with interest in use. Concerns included risk of psychosis, lack of trained providers, and potential for exploitation. No demographic factors were associated with interest or levels of distress.This pilot study provides insights into the attitudes and concerns toward PAT among patients with incurable illnesses. Over half of participants expressed interest. However, concerns regarding its use were identified, with patients' concern for the risk of exploitation associated with PAT as an especially novel concern documented in this patient population. This highlighted the need for further education of risks and benefits or PAT by trained clinicians and rigorous training of clinicians with the establishment of safeguards against exploitation. Further research is necessary to explore the potential benefits of PAT and related non-psilocybin psychedelic compounds in addressing existential distress among patients with incurable illnesses.